“Determinación de las curvas de absorción de fósforo y potasio en el cultivo de sacha inchi ( piukenetia volubilis L.) bajo las condiciones de bello horizonte” - Guerrero Abad, Roger Arbildo (2014)
Behavior of phosphorus and potassium was studied by culturing sacha inchi (Plukenetia vol u bilis L.) under conditions of Bello Horizonte - T arapoto, in which the absorption curve was determined; the absorption and removal of phosphorus and potassium in connection with crop phenology. He used a DBCA consisting of three treatments and four replications, using as a source of phosphorus triple and potassium chloride potassium superphosphate. Analysis of tissues (root, stem, leaf, flower and fruit) was performed, defining the most important phenological stages of the crop cycle; assessments were performed at 75, 112, 150 and 225 days after sowing (das) taking one sample per treatment in each phenological stage to give the fresh weight of each body befare being sent to the laboratory for their respective UNALM nutritional analysis, the method used for the determination of phosphorus and potassium was to Kjeldahl. By registering to the 225 days after planting in root accumulation of 3, 107 kg K has-1• in the leaf was 17.93 kg K ha-1 and at the stem 26 018 kg K ha -1 fruit 31.99 kg K has·1siendo organ q scored higher absorption of potassium, also to the 225 days after planting in root accumulation of 0.56 kg P ha-1, in the sheet was 3.31 kg P ha-1 and at the stem 6.47 kg P ha-1 the result 6.19 kg P ha1 siendo q obtained majar organ phosphorus absorption. Keywords: Potassium chloride: a metal halide compound is potassium and chlorine. In your state Pure is odorless. TSP: Product obtained by reaction of mineral phosphate with phosphoric acid and containing monocalcium phosphate as an essential component.